Design and fabrication of electrospun polycaprolactone/chitosan scaffolds for ligament regeneration - İNAN, AHMET TALAT; ŞAHİN, ALİ; YILMAZ, BETÜL; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Tendon and ligament impairments are among the most familiar injuries of the knee with acute or chronic pain conditions. The defects of anterior cruciate ligament (ACL) stay a known clinical problem. In the present study, the electrospinning method was used to fabricate 10wt.%PCL/(1, 3, 5)wt.%Chitosan (CS) appropriate and biocompatible scaffolds with a similar connective ligament geometry and structure. 10wt.%PCL/3wt.%CS demonstrated higher tensile strength value (0.58854 MPa) than other scaffolds in the tensile test. Moreover, 10wt.%PCL/3wt.%CS scaffolds had high mesenchymal stem cells (MSCs) viability value for all incubation periods. Swelling and degradation behaviours of the ligament-like scaffolds were examined in vitro for 15 days. Results reported that the highest swelling ratio was observed with CS addition for 10wt.%PCL/5wt.%CS scaffolds which value nearly reached to the 270% ratio. Scanning electron microscope proved the geometry of the scaffolds, which were suitable for ligament-like tissue. Attachment of MSCs on the scaffolds proved the network-like structure of the cells on the scaffolds.
Keywords: Anterior cruciate ligament (ACL); Chitosan; PCL; Ligament; Scaffold